Keraguan-Keraguan Terhadap Agama : Naturalisme: Agama, Paham, Naturalisme - Sururin Marfuah (Jurnal Penelitian Multidisiplin, 2022)
Naturalism holds that there is no mystery in nature because it moves and changes. Cause and effect determine the future. Since religion plays such an important role in people's lives, it is very important for communities to maintain their religious practices. The flow of naturalistic philosophy is one of the many schools of philosophy. The Aristotelian-Thomistic school of educational philosophy provides research on naturalistic philosophy. According to naturalism, no one is born with vices; on the contrary, everyone born on this planet basically has positive tendencies or traits. So what exactly is meant by